Lumbar Spinal Surgery in Patients With Parkinson Disease: A Multicenter Retrospective Study. Issue 6 (July 2017) - Kimura, Hiroaki; Fujibayashi, Shunsuke; Otsuki, Bungo; Takemoto, Mitsuru; Shikata, Jitsuhiko; Odate, Seiichi; Matsushita, Mutsumi; Kusuba, Akira; Kim, Youngwoo; Sakamoto, Takeshi; Watanabe, Kei; Ota, Masato; et al.
Abstract : Study Design: A multicenter, retrospective study. Objective: To identify the factors that affect surgery-related complications and to clarify the surgical strategy for treating lumbar disorders in Parkinson disease (PD). Summary of Background Data: Previous studies have reported a high complication rate for spinal surgery in patients with PD. Because of the limited number of studies, there are no guidelines for spinal surgery for PD patients. Methods: We retrospectively reviewed the records for 67 PD patients who underwent lumbar spinal surgery. The patients were divided into 3 groups: 12 patients underwent laminectomy (Laminectomy), 24 underwent fusion surgery (Fusion) for lumbar canal stenosis, and 31 underwent corrective surgery for spinal deformity (Deformity). We assessed surgery-related complications in each group. The Cox proportional hazards model was used to identify the factors that predicted surgical failure. Results: The percentages of patients who experienced failure of the initial surgery were 33.3% in the Laminectomy group, 45.8% in the Fusion group, and 67.7% in the Deformity group. The rates of implant failure were high in the Fusion and Deformity groups (33.3% and 38.7%, respectively). The Deformity group had a high rate of postoperative fracture (41.9%). These complications occurred at the most caudal site within a year after surgery and resulted in progression of kyphotic deformity. Multivariate analysis revealed that preoperative lumbar lordosis angle (LL) (per −1 degree) was associated with a failure of the initial surgery (hazard ratio, 1.024; 95% confidence interval, 1.008–1.04; P =0.003). Conclusions: We have demonstrated that a small preoperative LL increases the risk for failure of the initial surgery. Attaining and maintaining the proper lumbar lordosis with rigid fixation may be necessary in PD patients with a small preoperative LL.